Public Works as a Productive Safety Net in a Post-Conflict Setting : Evidence from a Randomized Evaluation in Sierra Leone - Rosas, Nina (World Bank, Washington, DC, 2016)
This paper examines the short-term impacts of a labor-intensive public works program on household welfare and economic prospects. Using a community-level randomized control trial approach, the paper finds that the public works program targeted at youth in Sierra Leone successfully provided temporary employment to youth characterized by low educational attainment. Cash income among program participants increased by nearly three times relative to the control counterparts, and treatment households experienced a 29 percent rise in monthly income. There is also evidence of significant re-optimization of household labor allocation and expenditure in response to program participation. First, there is an overall crowding-in of labor force participation by household members beyond program participation. Second, the extra income is spent partly to improve the quality of life and partly to secure future earnings. The treated households raised spending on food, medicines, and assets. They also expanded utilization of health services. Meanwhile, the consumption of temptation goods was greater, albeit by a small amount, and the rate of absenteeism among students was higher. To secure future earnings, the treated households set up new businesses: they were nearly four times more likely than the control households to set up new household enterprises. They also boosted their participation in informal savings groups and their investments in their homes and existing businesses. These results demonstrate that public works interventions have considerable potential as productive safety nets in post-conflict settings such as Sierra Leone. They can provide immediate income support, but also open avenues for investment in the productive capacity of poor households.